E-Learning Platform For Collaborative Coding Assignments - Chong, Mum Khong (2021)
Ever since the pandemic rampages across the world, university students in Malaysia who partake in programming courses are having difficulty collaborating with each other in their group projects due to restriction rules imposed to combat the virus. Inefficient conventional social media, lack of features in the current platforms had added insult to injury on this matter. Background studies was conducted through literature review for the problems, solutions and similar applications on the market to justify the need for such system and possible technologies or features that can be incorporated into the system design. The platform comes with two different modules or interface for different users, namely students and lecturers. Methodology-wise, parallel model was adopted to implement the different modules concurrently. Figma was used to product wireframes for the screens of the system. The technologies used are Vue.js, Vuetify, Node.js, Express.js, TypeScript, Socket.io, Nodemailer, NodeSchedule, Git, GitHub, Firebase and other third-party open-source packages for implementation of the system. The system was developed to mitigate the dilemma that students faced, moreover improving the transparency of the students’ progress by allowing lecturers to check on their work at any time. Students can collaborate in their coding assignments on the platform with rich functionalities provided such as real-time editor, chatting system, assignment management etc. whereas lecturers can freely check on any of their student groups to follow up their progress and even join their discussions to improve the assignment quality. With this platform, students and lecturers are able to communicate effectively on their work and provide efficient collaboration among group members for group coding assignments.